2015
DOI: 10.1103/physrevb.92.081115
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spin susceptibilities and superconductivity inHgBa2CuO4+δfrom nuclear magnetic resonance

Abstract: Nuclear magnetic resonance (NMR) experiments on single crystals of HgBa2CuO 4+δ are presented that identify two distinct temperature-dependent spin susceptibilities: one is due to a spin component that is temperature-dependent above the critical temperature for superconductivity (Tc) and reflects pseudogap behavior; the other is Fermi-liquid-like in that it is temperature independent above Tc and vanishes rapidly below Tc. In addition, we demonstrate the existence of a third, hitherto undetected spin susceptib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 30 publications
4
52
0
Order By: Relevance
“…χ levels off above about 250 K and decreases with cooling to T c = 98 K, which is a pseudogap behavior. Since the temperature dependence of χ resembles those of the plane-site 63 Cu and 17 O Knight shifts [7][8][9], one may regard the present bulk magnetic susceptibility χ as an intrinsic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…χ levels off above about 250 K and decreases with cooling to T c = 98 K, which is a pseudogap behavior. Since the temperature dependence of χ resembles those of the plane-site 63 Cu and 17 O Knight shifts [7][8][9], one may regard the present bulk magnetic susceptibility χ as an intrinsic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In NMR, one finds various degrees of line broadening in the various cuprates (see e.g., [24]) typically caused by concomitant charge and spin density variations [25]. The results cannot be dismissed as being due to sample quality, since even chemically highly ordered systems can show tremendous electronic inhomogeneity [26][27][28]. More recently, as will be addressed below, even the magnetic field was shown to influence the NMR splittings [29] and broadening [30].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Hg NMR showed that also the optimally doped system is not a single fluid [56]. In order to understand this somewhat mysterious behavior, more systems were studied [27]. With the new samples, it became apparent that there was a third shift component that had a different Cu shift anisotropy, easily recognizable for underdoped and overdoped samples.…”
Section: Failure Of the Single Fluid Modelmentioning
confidence: 99%
See 2 more Smart Citations